Assessment of thymoquinone effects on apoptotic and oxidative damage induced by morphine in mice heart - Jalili, Cyrus; Sohrabi, Maryam; Jalili, Faramarz; Salahshoor, Mohammad Reza (Cellular and Molecular Biology, 2018)
Opioids bind to specific receptors that are located in the central nervous system (CNS) and many other organs such as cardiovascular tissue. Morphine binds to opioid receptors and can induce oxidative stress under some certain conditions. Thymoquinone (TQ) has shown many therapeutic effects such as anti-inflammatory, antioxidant and immunomodulatory ones. Considering the oxidative effects of morphine, antioxidant effects of TQ and effects of oxidative damage in various types of biomolecules, the present study was conducted to determine the effect of morphine plus TQ on the expression of apoptotic genes in the heart of male mice. Hence we used real-time PCR to identify alterations in mRNA expression of genes involved in apoptotic pathway, including p53, Bax and Bcl-2 between the morphine-treated and TQ plus morphine-treated mice. Serum nitric oxide (NO) (Griess assay) and total antioxidant capacity (TAC) were analyzed and compared. In the morphine group, compared to control group, a significant increase in P53 and Bax mRNA expression and a significant decrease in Bcl-2 mRNA expression were observed (p < 0.01). In TQ plus morphine groups, NO was decreased (P <0 .001) and TAC levels were increased significantly (P < .001). Interestingly, TQ (9 and 18 mg/kg) plus morphine caused a significant decrease in p53 and Bax and a significant increase in Bcl2 mRNA expression, compared to morphine-treated group (p < 0.01). Collectively, the results of this study indicated that TQ, as an antioxidant, can improve the apoptotic effects induced by morphine in the heart tissue of mice.